Muhammad Shalih as-Samarani dalam Kacamata Masyarakat Muslim Milenial - Aflahal Misbah (Millati: Journal of Islamic Studies and Humanities, 2018)
Muhammad Salih As-Samarani was one of the Nusantara's intellectual figures of the past which was associated with the term 'Islam Nusantara'. This figure, in some of 'Islam Nusantara' literatures, is considered as one of the representative figures to explore and discover the foundation of 'Islam Nusantara'. His actions and thoughts in the 19th century in Java, which were able to connect Mecca and Pesantren and Pesantren and society, were indeed not negligible in the effort to build 'Islam Nusantara' argument. Recognition of the As-Samarani figure, in fact, is not only a field of scientific study for scholars, but also for ordinary people who are also increasingly keen to introduce As-Samarani in public. In this paper, as a preliminary study, the author tries to focus on seeing how As-Samarani is represented in public by ordinary people through YouTube. Almost all of the videos on Youtube which try to re-display As-Samarani figure appeared after the 'Islam Nusantara' become the 33rd NU Congress in Jombang. As-Samarani's figure on Youtube shows that along with the affirmation of the term 'Islam Nusantara', the As-Samarani figure is even more interesting for ordinary people, especially in media of his magical power contexts (such as turning stones into gold, meeting Imam Ghazali, his goats are able to defeat tigers), not his actions and thoughts, or more specifically perhaps his writings.